Ontworpen voor de eeuwigheid. De memoriesculptuur voor Joost Sasbout en Catharina van der Meer in de Eusebiuskerk te Arnhem (Bulletin KNOB, 2020)
The monument for Joost Sasbout and Catharina van der Meer in the Eusebius Church in Arnhem is a remembrance sculpture from the mid-16th century. Joost Sasbout was appointed chancellor of the newly founded court of justice in Arnhem, after the duchy of Gelre had come under Habsburg rule in 1543. Joost Sasbout died in 1546 and was buried in a tomb in the Eusebius Church, while his wife, Catharina, was buried in The Hague when she died in 1560.The sculpture featured a religious representation of The Birth of Christ, which is now gone. The inscriptions underneath, carved as if they were written on parchment, keep the memory of the deceased couple alive. There is also vanitas symbolism in the shape of cadaver images and putti with torches. The captions with the putti, Homo bulla and Caro fenum underline the vanitas idea, as does the inscription in the lower part of the sculpture. The whole thing is placed against a background of classical and grotesque motifs, kept together by a candelabra-like structure and scrollwork. The sculpture was most probably made by Colijn de Nole.It has often been argued in the past that this work originally looked differently and that parts of the current sculpture were added later. However, closer inspection reveals that there are no indications to support this theory. On the contrary, the fact that the entire monument was originally made of Avender stone, a not too obvious choice for Arnhem, supports the idea that the sculpture was indeed created in full at once.The inscriptions also hold no clues as to different histories of development of parts of the sculpture. Nor does the ‘stacked’ character of the composition, when we compare this sculpture with the mantelpiece in the Sheriff’s Courtroom in the Old Town Hall of Kampen, which is the only work that can definitely be ascribed to Colijn de Nole. In this work too, for example, the frames do not exactly line up. The description of the monument by Calvete de Estrella in 1549 provides the proof for the line of reasoning with regard to the sculpture’s genesis. Finally, going by the inscription in the lower part of the work, it looks as if Joost Sasbout was personally involved in the design for the remembrance sculpture, although we cannot be certain whether this actually was the case.